TREATMENT OF NON-EPHITHELIAL MALIGNANT TUMОRS OF MAXILLA, NASAL CAVITY AND PARANASAL SINUSES (IMMEDIATE RESULTS) - A. I. Khasanov; R. M. Beckmirzayev; B. Yu. Yusupov (Опухоли головы и шеи)
Background: to examine the role of long-term intra-arterial chemotherapy (CT) for therapy of patients with non-epithelial malignant tumors of maxilla, nasal cavity and paranasal sinuses.Material and methodology of the study. 38 patients with non-epithelial malignant tumors of maxilla, nasal cavity and paranasal sinuses received therapy during the period from 2000 to 2008 and in 2014. Osteosarcoma was revealed with 12 (31.5 %) of patients. Depending on the therapy method, the patients were divided into 4 groups: 1) long-term intra-arterial CT with local ultra-high-frequency hyperthermia and radiation therapy (RT) (n = 10); 2) long-term intra-arterial CT and RT (n = 13); 3) systemic polyCT and RT (n = 6); 4) RT with subsequent surgery (n = 9). The following scheme was used by us most frequently: cisplatin with the total dose of 100 mg; total dose with the total dose of 60 mg and cyclophosphamide with the total dose of 1,000 mg, but intramuscularly. Long-term regional intra-arterial chemotherapy was performed for patients of the 1st  and the 2nd  group by ligation and catheterization of the external carotid artery. The degree of toxicity of the CT was determined by the NCIC-СТС scale of the WHO.Results and discussion. The highest toxicity was observed in the 3rd  group of patients treated with CT intravenously. In its turn, increasing of the frequency of local side effects in the form of the stomatitis of the II and the III degree was observed in the 1st and the 2nd group as compared to the 3rd group of patients. General toxicity to which nausea, vomiting, leukopenia was attributed was most expressed in the 3rd group Objective (full + partial) effect was reached in the 1st group of 10 patients with 9 patients (90 %), in the 2 nd  group of 13 patients with 11 patients (84.6 %), and in the 3rd group of 6 patients with 3 patients (50 %). This is associated with the fact that the concentration of chemical drugs in the tumor is increased as a result of regional intra-arterial CT, which allowed achieving the maximum tumor damage with minimum effect of chemical drugs on various organs and systems of the organism and favored decreasing of toxicity of chemical drugs as compared to the 3 rd group of patients that received systemic CT by intravenous dripping.Conclusions. The patients that received neoadjuvant regional intra-arterial CT demonstrated the direct effect of therapy higher than the ones that received systemic CT. Long-term intra-arterial CT delivers the chemical drug directly to the center of the tumor lesion and creates the maximum concentration and prolonged contact of the chemotherapy drug with the tumor.